Anomalous chlorofluorocarbon uptake by mesoscale eddies in the Drake Passage region. Issue 2 (23rd February 2015) - Song, Hajoon; Marshall, John; Gaube, Peter; McGillicuddy, Dennis J.
Abstract: The role of mesoscale eddies in the uptake of anthropogenic chlorofluorocarbon‐11 (CFC‐11) gas is investigated with a 1/20° eddy‐resolving numerical ocean model of a region of the Southern Ocean. With a relatively fast air‐sea equilibrium time scale (about a month), the air‐sea CFC‐11 flux quickly responds to the changes in the mixed layer CFC‐11 partial pressure ( p CFC‐11). At the mesoscale, significant correlations are observed between p CFC‐11 anomaly, anomalies in sea surface temperature (SST), net heat flux, and mixed layer depth. An eddy‐centric analysis of the simulated CFC‐11 field suggests that anticyclonic warm‐core eddies generate negative p CFC‐11 anomalies and cyclonic cold‐core eddies generate positive anomalies of p CFC‐11. Surface p CFC‐11 is modulated by mixed layer dynamics in addition to CFC‐11 air‐sea fluxes. A negative cross correlation between mixed layer depth and surface p CFC‐11 anomalies is linked to higher CFC‐11 uptake in anticyclones and lower CFC‐11 uptake in cyclones, especially in winter. An almost exact asymmetry in the air‐sea CFC‐11 flux between cyclones and anticyclones is found. Key Points: Anticyclonic (cyclonic) eddies generate negative (positive) p CFC‐11 anomalies Mixed layer dynamics is the key process that modulates the surface p CFC‐11 Anticyclones lead to a slight increase in the net uptake of CFC‐11